Pengaruh Bantuan Langsung Tunai Dan Pendapatan Usaha Terhadap Kesejahteraan Pelaku Usaha Mikro Kecil Menengah Pada Masa Penyebaran Covid-19 - Sefnat Aristarkus Tang; Yustina Maro; Junius M. Sau Sabu (Peneliti.net, 2022)
Welfare is an organized system implemented through social services and institutions to assist individuals and groups to attain a satisfactory standard of life and health as well as social and social relations which provide an opportunity for them to develop to the fullest their abilities and to improve their well-being according to the needs of the family and society. This research aims to determine the effect of Direct Cash Assistance (BLT) and Business Income on the Welfare of Micro, Small, and Medium Enterprises (MSMEs) During the Spread of Covid-19. The research was conducted in Kelurahan Kalabahi Kota Teluk Mutiara District, Alor Regency with a sample of 30 people. Collecting data using observation, interviews, questionnaires, and literature study. The results showed that partially the Direct Cash Assistance variable did not affect the welfare of MSME actors with a significant value of 0.579 ≥ 0.05. Partially, the variable Operating Income has a significant effect on the Welfare of MSME Actors indicated by a significance value of 0.000 <0.05. Simultaneously, the direct cash assistance and business income variables have an effect on the welfare of MSME actors as shown by the significance value of the F test of 0.000.